2002
DOI: 10.1007/s007950200021
|View full text |Cite
|
Sign up to set email alerts
|

Typical nemaline bodies presenting in a patient with polymyositis

Abstract: A 66-year-old woman presented with a progressive myopathy affecting the proximal limbs and unusual pathological findings of nemaline bodies on muscle biopsy. Histological examination demonstrated that the bodies were mainly located in the subsarcolemmal region of atrophic fibers, exhibited strong immunoreactivity with antibodies to both alpha-actinin and m-actin, and had a typical lattice-like appearance at higher magnification on electron microscopy. These findings were the same as those for nemaline myopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Indeed, nemaline bodies can be found in several neuromuscular disorders other than nemaline myopathy. 13,14 Whether or not nemaline rods diminished in our patient with treatment is not known, as a muscle biopsy was not performed after clinical improvement. In nemaline myopathy, an increase of alpha-actinin has been reported in patients with mutations in the muscle alphaskeletal actin gene (ACTA1).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, nemaline bodies can be found in several neuromuscular disorders other than nemaline myopathy. 13,14 Whether or not nemaline rods diminished in our patient with treatment is not known, as a muscle biopsy was not performed after clinical improvement. In nemaline myopathy, an increase of alpha-actinin has been reported in patients with mutations in the muscle alphaskeletal actin gene (ACTA1).…”
Section: Discussionmentioning
confidence: 97%
“…The absence of nemaline bodies at a stage when clinical symptoms were already apparent and the muscle biopsy showed myopathic changes may indicate that they occur secondarily in the course of disease. Indeed, nemaline bodies can be found in several neuromuscular disorders other than nemaline myopathy . Whether or not nemaline rods diminished in our patient with treatment is not known, as a muscle biopsy was not performed after clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that NB per se is not specific although its presence is a mandatory finding of nemaline myopathies. NB can be observed also in idiopathic inflammatory myopathies, alcoholic myopathy, advanced stage of muscular dystrophies, hypothyroidism, cancer invasion, and chronic neuropathy like spinal muscular atrophy [37][38][39][40][41][42]. Empirically, a small number of fibers with NB can be seen physiologically if the muscle is biopsied near tendon.…”
Section: Muscle Pathologymentioning
confidence: 99%
“…This suggestion is proved by clinical studies data, which have shown nemaline bodies and cap structures to occur in a muscle fiber after other clinical evidences of the disease have developed [13]. In addition, the presence of nemaline bodies may be an epiphenomenon of other diseases such as human immunodeficiency virus infection or polymyositis [14,15] and present normally in some muscles (extraocular, myotendinous junctions) and in the muscles of aged persons [16]. The mechanisms of appearance of the abnormal protein aggregates within the sarcomere and those underlying the disturbance of contractile function remain unclear and occupy researchers’ close attention in recent years.…”
Section: Introductionmentioning
confidence: 98%